Peltier cooling in molecular junctions - Cui, Longji; Miao, Ruijiao; Wang, Kun; Thompson, Dakotah; Zotti, Linda Angela; Cuevas, Juan Carlos; Meyhofer, Edgar; Reddy, Pramod (My University, 2018)
The study of thermoelectricity in molecular junctions is of fundamental interest for the development of various technologies including cooling (refrigeration) and heat-to-electricity conversion1-4. Recent experimental progress in probing the thermopower (Seebeck effect) of molecular junctions5-9has enabled studies of the relationship between thermoelectricity and molecular structure10,11. However, observations of Peltier cooling in molecular junctions-a critical step for establishing molecular-based refrigeration-have remained inaccessible. Here, we report direct experimental observations of Peltier cooling in molecular junctions. By integrating conducting-probe atomic force microscopy12,13with custom-fabricated picowatt-resolution calorimetric microdevices, we created an experimental platform that enables the unified characterization of electrical, thermoelectric and energy dissipation characteristics of molecular junctions. Using this platform, we studied gold junctions with prototypical molecules (Au-biphenyl-4,4'-dithiol-Au, Au-terphenyl-4,4''-dithiol-Au and Au-4,4'-bipyridine-Au) and revealed the relationship between heating or cooling and charge transmission characteristics. Our experimental conclusions are supported by self-energy-corrected density functional theory calculations. We expect these advances to stimulate studies of both thermal and thermoelectric transport in molecular junctions where the possibility of extraordinarily efficient energy conversion has been theoretically predicted2-4,14.
Keywords: Molecular electronics, Scanning probe microscopy; 530